Variability of blood eosinophils in patients in a clinic for severe asthma. Issue 2 (14th January 2019) - Rakowski, Ewa; Zhao, Sibo; Liu, Mengling; Ahuja, Shilpi; Durmus, Nedim; Grunig, Gabriele; Curotto de Lafaille, Maria; Wu, Yinxiang; Reibman, Joan
Summary: Background: Blood eosinophils are used to determine eligibility for agents targeting IL‐5 in patients with uncontrolled asthma. However, little is known about the variability of blood eosinophil measures in these patients before treatment initiation. Objective: To characterize variability and patterns of variability of blood eosinophil levels in a real‐world clinic for severe asthmatics. Methods: Retrospective review of blood eosinophils measured over a 5‐year period in patients enrolled in an urban clinic. Repeated measures of blood eosinophil levels in individuals were evaluated, and cluster analysis was performed to characterize patients by eosinophil patterns. Clinical characteristics associated with eosinophil levels and patterns of variability were analysed. Results: Patients treated in the Bellevue Hospital Asthma Clinic within a 3‐month period were identified (n = 219). Blood eosinophil measures were obtained over the previous 5 years. Only 6% (n = 13) of patients had levels that were consistently above 300 cells/μL. Nearly 50% (n = 104) had eosinophil levels that traversed the threshold of 300 cells/μL. In contrast, 102 (46%) had levels that never reached the threshold of 300 cells/μL. Cluster analyses revealed three clusters with differing patterns of levels and variability. There was a suggestion of decreased clinical control and increased atopy in the cluster with the greatest variability in blood eosinophil measures. Conclusion: In an urban clinic for patients referred for uncontrolled asthma, blood measures of eosinophils were variable and showed differing patterns of variability. These data reinforce the need to perform repeated eosinophil blood measures for appropriate designation for therapeutic intervention.